Statistical Analysis Dataset Based on Taguchi Design and Regression Modeling - Kolesnyk, Vitalii; Dovhopolov, Andrii; Andrii Deineka (DataverseUA, 2026)
The dataset is intended for statistical analysis of the results of numerical experiments using the Taguchi design of experiments and regression analysis, as implemented in the Minitab software environment. Within the framework of data processing, Taguchi orthogonal designs were employed to assess the influence of control factors, calculate signal-to-noise ratios for robustness analysis, and plot main effects and rank factors by their contribution to the response. Additionally, regression modeling was performed to establish functional dependencies between process parameters and quantitative response characteristics, to check the statistical significance of coefficients, and to analyze the adequacy of the models. The dataset can be used to reproduce the analysis, compare statistical approaches, educational goals, and further develop mathematical models in engineering problems.